Sustainability Through Extroversion: The Curious Case of Municipal and Public Libraries in Greece - Katsira, Georgia; Koulouris, Alexandros (European Journal of Sustainable Development, 2023)
Public and municipal libraries, besides being keepers of local community documents and books, are - or should be - modern hubs of knowledge and diffusers of information to the community that surrounds them. This article reveals the areas of extroversion that municipal and public libraries can undertake, focusing on the efforts they need to make in order to best interact with local communities, going beyond their traditional usage of addressing only their patrons. Furthermore, the results of a survey conducted in the frame of the 4th Panhellenic Public Libraries Conference are presented, showing how much extroverted librarians working in public and municipal libraries are considered, as well as what kind of extroversion programs they implement in their library. Keywords: public libraries, municipal libraries, extroversion, innovation, sustainability of libraries, lifelong learning, information literacy